2022
DOI: 10.1186/s40644-022-00480-4
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling and diffusion-weighted imaging for identification of retropharyngeal lymph nodes in patients with nasopharyngeal carcinoma

Abstract: Background To evaluate the parameters derived from arterial spin labeling (ASL) and multi-b-value diffusion-weighted imaging (DWI) for differentiating retropharyngeal lymph nodes (RLNs) in patients with nasopharyngeal carcinoma (NPC). Methods This prospective study included 50 newly diagnosed NPC and 23 healthy control (HC) participants. RLNs of NPC were diagnosed according to the follow-up MRI after radiotherapy. Parameters derived from ASL and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Our study discovered that mean ADC was significantly higher for malignant than benign nodes, albeit with a prominent overlap in distribution. Despite numerous studies presenting a considerably lower ADC value for metastatic lymph nodes compared to benign ones [ 20 24 ], several studies have yielded a result similar to our research, substantiating a significantly elevated ADC value for metastatic lymph nodes in HNSCC [ 25 , 26 ]. A study by Lim et al found no substantial ADC variation between benign and malignant cervical small lymph nodes [ 8 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our study discovered that mean ADC was significantly higher for malignant than benign nodes, albeit with a prominent overlap in distribution. Despite numerous studies presenting a considerably lower ADC value for metastatic lymph nodes compared to benign ones [ 20 24 ], several studies have yielded a result similar to our research, substantiating a significantly elevated ADC value for metastatic lymph nodes in HNSCC [ 25 , 26 ]. A study by Lim et al found no substantial ADC variation between benign and malignant cervical small lymph nodes [ 8 ].…”
Section: Discussionsupporting
confidence: 86%